Testing conditions for reversibility of martensitic transformations with an isotropic potential for identical particles - Laguna, Maria Fabiana (2014)
A simple interparticle potential for a set of classical identical particles is used to model martensitic transformations in two dimensions. The influence of the symmetry of the phases involved in the transformation on the reversibility of such process is analyzed. Numerical simulations are used to confirm the theoretical suggestion that a necessary condition for reversibility is that transformations be group–subgroup.